A lithium-ion battery electrolyte and lithium-ion battery of high-nickel ternary / silicon-carbon system
By adding phosphate additives to the high-nickel ternary/silicon carbon system lithium-ion battery electrolyte, a stable passivation film is formed, which solves the problems of transition metal dissolution and silicon particle expansion, and significantly improves the cycle stability of the battery.
Patent Information
- Application Number
- CN202211053263.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-08-31
AI Technical Summary
During the circulation process, the lithium-ion battery with high nickel ternary/silicon carbon anode system has continuous electrolyte consumption and interface impedance growth caused by transition metal dissolution and silicon particle expansion, which deteriorates the cycle life.
The electrolyte solution is formed by a positive electrode reaction, which inhibits the dissolution of transition metals, and reacts in the silicon negative electrode to form an organic-inorganic composite flexible passivation film, which inhibits the expansion of silicon particles and the consumption of electrolyte.
Effectively reduce irreversible capacity loss, reduce interface impedance, and improve the cycle stability of high-nickel ternary/silicon carbon system lithium-ion batteries.
Smart Images

Figure CN115377495B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery electrolyte and a lithium ion battery of a high-nickel ternary / silicon-carbon system. Background Art
[0002] As consumers' requirements for the range of pure electric vehicles become higher and higher, the demand for high energy density of lithium-ion batteries is becoming more and more urgent. With the development of battery electrode materials, lithium-ion battery technology has developed rapidly. At present, lithium-cobalt batteries have expanded to battery systems such as ternary systems, lithium manganese oxide, lithium iron phosphate, and silicon-carbon negative electrodes. The new silicon-carbon negative electrode lithium-ion battery breaks through the inherent limitations of graphite as a negative electrode, and its performance is significantly better than that of traditional lithium-ion batteries.
[0003] At present, there are also many problems in the application of high-nickel ternary / silicon-carbon negative electrode system lithium-ion batteries. Among them, the transition metal dissolves in the high-nickel ternary material during the cycle and reacts with the electrolyte; the volume expansion and contraction of the silicon-carbon negative electrode during the cycle causes the particles to pulverize and fall off, and the continuous reaction of the electrolyte to generate SEI film components causes the interfacial impedance to increase, which deteriorates the cycle life of the lithium-ion battery.
[0004] The present invention provides a feasible solution to the defects in the application of lithium-ion batteries with a high-nickel ternary / silicon-carbon negative electrode system. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a lithium-ion battery electrolyte and a lithium-ion battery of a high-nickel ternary / silicon-carbon system, which use phosphate additives to form a film in the positive electrode reaction, inhibit the dissolution of transition metals in the positive electrode material, and reduce the irreversible capacity loss; at the same time, the silicon negative electrode reaction generates an organic-inorganic composite flexible passivation film, which inhibits the continuous consumption of electrolyte caused by the expansion of silicon particles during the cycle, reduces the interface impedance, and thereby improves the cycle stability of the high-nickel ternary / silicon-carbon system lithium-ion battery.
[0006] The present invention provides a high-nickel ternary / silicon-carbon system lithium-ion battery electrolyte, comprising the following components: a lithium salt, an organic solvent, a film-forming additive and a phosphate additive; the structural formula of the phosphate additive is shown in formula (I):
[0007]
[0008] Wherein, R1 is selected from aryl, C1-C3 alkyl or fluoroalkyl; R2 and R3 are each independently selected from aryl, F, C1-C3 alkyl or fluoroalkyl.
[0009] The phosphate additive in the present invention is 2,2-dialkyl-1,3-dioxolane-4,5-diol propenyl phosphate, and its structural formula is shown in formula (I).
[0010] Preferably, the mass of the phosphate additive accounts for 0.1-5% of the total mass of the electrolyte.
[0011] Preferably, the lithium salt is one or a combination of lithium chloride, lithium fluoride, lithium nitrate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorophosphate.
[0012] Preferably, the organic solvent is one or a combination of more than one of dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, ethyl formate, ethyl acetate, ethyl propionate, ethyl butyrate, methyl propionate and tetrahydrofuran.
[0013] Preferably, the film-forming additive is one or a combination of more than one of vinyl sulfate, vinylene carbonate, propylene sulfite, fluoroethylene carbonate, cyclohexylbenzene, and vinyl ethylene carbonate.
[0014] Preferably, based on the total mass of the electrolyte, the mass percentages of the following components are: 10-15% of lithium salt, 1-5% of film-forming additive, 0.1-5% of phosphate additive, and the balance is organic solvent.
[0015] The present invention also proposes a high-nickel ternary / silicon-carbon system lithium-ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the active material of the positive electrode is a high-nickel ternary positive electrode material, the active material of the negative electrode is a silicon-carbon negative electrode material, and the electrolyte is the electrolyte described in any one of claims 1 to 6
[0016] Beneficial effects: The present invention adds the functional additive 2,2-dialkyl-1,3-dioxolane-4,5-diol allyl phosphate to the electrolyte, which can generate a dense and stable passivation film at the positive and negative electrodes during the battery formation process. The positive electrode film formation can inhibit the dissolution of transition metals in the positive electrode material and reduce irreversible capacity loss; at the same time, the silicon negative electrode reacts to generate an organic-inorganic composite flexible passivation film, which inhibits the continuous consumption of electrolyte caused by the expansion of silicon particles during the cycle, reduces the interface impedance, and thus improves the cycle stability of high-nickel ternary / silicon-carbon system lithium-ion batteries. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is described in detail below through specific embodiments.
[0018] The phosphate ester additives 1-10 in the following examples are commercially available.
[0019] The film-forming additive in the following examples is composed of vinylene carbonate and vinyl sulfate in a mass ratio of 1:1.
[0020] Comparative Example 1
[0021] Preparation of electrolyte:
[0022] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50, and then 13.5% by mass of lithium hexafluorophosphate (LiPF6) is slowly added while slowly stirring until it is completely dissolved. Then, 3% by mass of a film-forming additive (1.5% vinylene carbonate, 1.5% vinyl sulfate) is added, and the basic electrolyte is prepared after stirring evenly.
[0023] Example 1
[0024] Preparation of electrolyte:
[0025] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:20:50, and then 13.5% by mass of lithium hexafluorophosphate (LiPF6) is slowly added while slowly stirring until it is completely dissolved. Then, 3% by mass of a film-forming additive and 1% by mass of a phosphate additive 1 are added, and the silicon-carbon electrolyte is obtained after stirring evenly.
[0026] Among them, the structural formula of the phosphate additive 1 is:
[0027] Example 2
[0028] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 2. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0029] Among them, the structural formula of the phosphate additive 2 is:
[0030] Example 3
[0031] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 3. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0032] Among them, the structural formula of the phosphate additive 3 is:
[0033] Example 4
[0034] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 4. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0035] Among them, the structural formula of the phosphate additive 4 is:
[0036] Example 5
[0037] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 5. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0038] Among them, the structural formula of the phosphate additive 5 is:
[0039] Example 6
[0040] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 6. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0041] Among them, the structural formula of the phosphate additive 6 is:
[0042] Example 7
[0043] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 7. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0044] Among them, the structural formula of the phosphate additive 7 is:
[0045] Example 8
[0046] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 8. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0047] Among them, the structural formula of the phosphate additive 8 is:
[0048] Example 9
[0049] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 9. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0050] Among them, the structural formula of the phosphate additive 9 is:
[0051] Example 10
[0052] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the phosphate additive, which is 1% by mass of the phosphate additive 10. The other components, contents and preparation methods are the same as those in Embodiment 1.
[0053] Among them, the structural formula of the phosphate additive 10 is:
[0054] Embodiment 11
[0055] The silicon-carbon electrolyte in this embodiment is different from that in Embodiment 1 only in the amount of phosphate ester additives and organic solvents. The mass percentage of the phosphate ester additive 1 is 0.1%, the composition and content of the lithium salt and the film-forming additive are the same as those in Embodiment 1, and the balance is the organic solvent; the preparation method is the same as that in Embodiment 1.
[0056] Example 12
[0057] The silicon-carbon electrolyte in this embodiment differs from that in Embodiment 1 only in the amount of phosphate ester additives and organic solvents used. The mass percentage of the acid ester additive 4 is 5%, the composition and content of the lithium salt and the film-forming additive are the same as those in Embodiment 1, and the balance is the organic solvent; the preparation method is the same as that in Embodiment 1.
[0058] The electrolytes in Comparative Example 1 and Examples 1 to 12 were respectively prepared into lithium ion batteries, and the specific preparation steps were as follows:
[0059] Preparation of positive electrode sheet: Active material lithium nickel cobalt manganese oxide (NCM811), conductive agent super conductive carbon (SP), and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in N-methyl-2-pyrrolidone solvent system at a mass ratio of 97:1:2, and the slurry was coated on the current collector Al foil. The positive electrode sheet was obtained by slitting, die cutting, and rolling. Its compaction density was 3.4g / cm 3 .
[0060] Preparation of negative electrode sheet: Silicon carbon negative electrode material (SiOC450), conductive agent super conductive carbon (SP), binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a deionized water solvent system at a mass ratio of 95:1:2:2, and the slurry was coated on the current collector Cu foil. After slitting, rolling and die cutting, the negative electrode sheet was obtained, and its compaction density was 1.6g / cm 3 .
[0061] Diaphragm preparation: 12 μm polypropylene (PP) base film is coated with 4 μm nano-aluminum oxide coating.
[0062] Battery preparation: stack the positive electrode sheet, separator and negative electrode sheet in sequence to obtain a bare cell according to the process of laminated battery, then pre-package the bare cell in an aluminum-plastic film, inject the prepared electrolyte and then package it to obtain the required soft-pack battery.
[0063] The electrical performance test of the lithium-ion battery prepared above is carried out as follows:
[0064] The above soft pack battery was formed and divided into different capacities using a battery test cabinet. The formation process was 0.02C constant current charging to 3.0V, 0.1C constant current charging to 3.4V, and 0.2C constant current charging to 3.7V; the aging process was 45°C for 12 hours; the division process was 0.33C constant current and constant voltage charging to 4.25V, the end current was 0.05C, and 0.33C constant current discharge was to 2.75V, repeated 3 times. Then the battery was charged and discharged at 1C / 1C constant current and constant voltage for 1000 cycles at room temperature, and the voltage range was set to 2.75-4.25V. After the cycle, the impedance of the battery was tested using an internal resistance meter, and the thickness of the battery was tested using a vernier caliper. The internal resistance growth rate was equal to the difference before and after the cycle divided by the internal resistance of the battery before the cycle, and the thickness growth rate was equal to the difference before and after the cycle divided by the thickness of the battery before the cycle. Comparing the internal resistance growth rate and thickness growth rate of the battery, the specific results are shown in Table 1.
[0065] Table 1 Battery cycle performance test results
[0066]
[0067]
[0068] Comparing the test results of the above-mentioned Examples 1 to 12 with those of Comparative Example 1, it can be seen that the electrolyte to which the phosphate ester additive 2,2-dialkyl-1,3-dioxolane-4,5-diol propenyl phosphate provided by the present invention is added significantly improves the initial charge and discharge coulomb efficiency and capacity retention rate in the soft-pack battery cycle test, reduces the growth rate of internal resistance and battery thickness, inhibits the impedance growth caused by the continuous reaction of the electrolyte during the cycle and the increase in the thickness of the battery cell caused by the expansion of silicon particles, and improves the cycle stability of the battery. The electrolyte provided by the present invention is an excellent electrolyte suitable for high nickel / silicon carbon system lithium ion batteries.
[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high nickel ternary / silicon carbon system lithium ion battery electrolyte, characterized in that: Includes the following components: Lithium salt, organic solvent, film-forming additive and phosphate additive; the structural formula of the phosphate additive is shown in formula (I): Wherein, R1 is selected from aryl, C1-C3 alkyl or fluoroalkyl; R2 and R3 are each independently selected from aryl, F, C1-C3 alkyl or fluoroalkyl.
2. The high nickel ternary / silicon carbon system lithium ion battery electrolyte according to claim 1, characterized in that: The mass of the phosphate additive accounts for 0.1-5% of the total mass of the electrolyte.
3. The high nickel ternary / silicon carbon system lithium ion battery electrolyte according to claim 1 or 2, characterized in that: The lithium salt is one or a combination of lithium chloride, lithium fluoride, lithium nitrate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorophosphate.
4. The high nickel ternary / silicon carbon system lithium ion battery electrolyte according to any one of claims 1 to 3, characterized in that: The organic solvent is one or a combination of dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, ethyl formate, ethyl acetate, ethyl propionate, ethyl butyrate, methyl propionate, and tetrahydrofuran.
5. The high nickel ternary / silicon carbon system lithium ion battery electrolyte according to any one of claims 1 to 4, characterized in that: The film-forming additive is one or a combination of more than one of vinyl sulfate, vinylene carbonate, propylene sulfite, fluoroethylene carbonate, cyclohexylbenzene, and vinyl ethylene carbonate.
6. The high nickel ternary / silicon carbon system lithium ion battery electrolyte according to any one of claims 1 to 5, characterized in that: Based on the total mass of the electrolyte, the mass percentages of the following components are: 10-15% of lithium salt, 1-5% of film-forming additive, 0.1-5% of phosphate additive, and the balance is organic solvent.
7. A high nickel ternary / silicon carbon system lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material of the positive electrode is a high-nickel ternary positive electrode material, the active material of the negative electrode is a silicon-carbon negative electrode material, and the electrolyte is the electrolyte described in any one of claims 1 to 6.
Citation Information
Patent Citations
Non-aqueous electrolyte and power storage device using same
CN104508896A
Lithium ion battery electrolyte suitable for high-nickel ternary / silicon carbon system
CN110931873A